2013
DOI: 10.1136/bmj.e8525
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent use of diuretics, angiotensin converting enzyme inhibitors, and angiotensin receptor blockers with non-steroidal anti-inflammatory drugs and risk of acute kidney injury: nested case-control study

Abstract: Objectives To assess whether a double therapy combination consisting of diuretics, angiotensin converting enzyme inhibitors, or angiotensin receptor blockers with addition of non-steroidal anti-inflammatory drugs (NSAIDs) and the triple therapy combination of two of the aforementioned antihypertensive drugs to which NSAIDs are added are associated with an increased risk of acute kidney injury.Design Retrospective cohort study using nested case-control analysis. Setting General practices contributing data to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
251
3
15

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 343 publications
(281 citation statements)
references
References 55 publications
(76 reference statements)
12
251
3
15
Order By: Relevance
“…Perhaps the most relevant examples are ACE inhibitors and ARBs, which are associated with functional AKI, particularly in the setting of acute hypovolaemia 5,[125][126][127] . These agents are frequently prescribed, particularly in the elderly 128 .…”
Section: Ace Inhibitors and Arbsmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps the most relevant examples are ACE inhibitors and ARBs, which are associated with functional AKI, particularly in the setting of acute hypovolaemia 5,[125][126][127] . These agents are frequently prescribed, particularly in the elderly 128 .…”
Section: Ace Inhibitors and Arbsmentioning
confidence: 99%
“…This approach is supported by the fact that each nephrotoxin administration presents a 53% greater odds of developing AKI 142 , and is compounded when patients receive more than one nephrotoxin 143 . Combining nephrotoxins can result in pharmacodynamic drug interactions, such as the 'triple whammy' of NSAIDs, diuretics and ACE inhibitors or ARBs 125 . In the non-ICU setting, escalating the burden of nephrotoxic medications from two to three medications more than doubles the risk of developing AKI, and 25% of non-critically ill patients who receive three or more nephrotoxins develop AKI 88,144 .…”
Section: Nephrotoxin Management During Akdmentioning
confidence: 99%
“…Recently, Lapi et al [13] documented an overall increased risk of acute kidney injury with a triple therapy combination but not with a double therapy combination in a retrospective study evaluating 487.372 patients. In fact, during the treatment with diuretics and NSAIDs (without an ACEI or an ARB), despite a reduction in renal blood flow (caused by diuretics) and the presence of renal afferent arteriolar constriction, glomerular filtration is probably maintained as a result of the effect of angiotensin II mediated efferent arteriolar vasoconstriction and sodium retention [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…The combination ofan angiotensin converting enzyme-inhibitor (ACEI) or an angiotensin II receptor blocker (ARB), a diuretic and a NSAID may increase the risk of acute kidney injury, calledtriple whammy, because each drug is able to affect kidney function through different mechanisms [12,13].In particular, diuretics can lead to hypovolaemia, ACE-inhibitors/ARBs cause haemodynamic decrease of glomerular filtration rate due to efferent arteriolar vasodilation, and NSAIDs inhibit prostacyclin synthesis (thus leading to renal afferent arteriolar vasoconstriction) [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Lapi et al reported a 30% increased incidence of AKI when patients were treated with this combination, especially at the start of treatment. 7 Our patient likely had a severe enough perturbation of the renal microcirculation to result in anuria, with blood flow, and pO 2 sufficient to prevent necrosis, but not enough to maintain the GFR 8 -a syndrome which perhaps could be described as ''acute renal autoregulatory dysfunction'' (''ARAD''). Despite the apparent decrease in her Pgc, flow through the efferent arteriole and the vasa recta presumably remained sufficient to maintain tubular integrity and avoid ATN, attested to by the increased urine osmolality and volume, and to the rapid recovery of renal function after the withdrawal of the offending medications and increasing her intravascular volume.…”
Section: Discussionmentioning
confidence: 99%